Mycobacterium tuberculosis inducing disseminated intravascular coagulation - Wang, Jann-Yuan; Hsueh, Po-Ren; Lee, Li-Na; Liaw, Yuang-Shuang; Shau, Wen-Yi; Yang, Pan-Chyr; Luh, Kwen-Tay (Thrombosis and Haemostasis, 2005)
Disseminated intravascular coagulation (DIC) can develop infrequently in patients with tuberculosis and has a very high mortality rate. We conducted a retrospective study to evaluate the incidence of tuberculosis-induced DIC and to investigate the clinical manifestation, outcome, and prognostic factors of such patients. From January 2002 to December 2003, all culture-proven tuberculosis patients who developed DIC before starting anti-tuberculosis treatments were selected for this study. Patients who had other clinical conditions or were infected by other pathogens that may have been responsible for their DIC were excluded. Survival analysis was performed for each variable with possible prognostic significance. Our results showed that 27 (3.2%) out of the 833 patients with culture-proven tuberculosis had tuberculosis-induced DIC with a mortality rate of 63.0%. The most common clinical manifestations were fever (63.0%) and multiple patches of pulmonary consolidation (59.3%). Seven (25.9%) patients had disseminated tuberculosis. Twelve (44.4%) developed acute respiratory distress syndrome and three (11.1%) were associated with hemophagocytosis. Twenty-four (88.9%) patients had findings that were unusual for an acute bacterial infection, such as positive acid-fast smear, miliary pulmonary lesions, lymphocytotic exudative pleural effusion, and mediastinal lymphadenopathy. Early anti-tuberculosis treatment significantly improved survival. In conclusion, tuberculosis can cause DIC. Patients with non-miliary, non-disseminated tuberculosis could also develop the rare clinical manifestation. Since the prognosis was very poor in patients not treated at an early stage, a high index of suspicion is required, especially in those with clinical findings suggestive of tuberculosis.
Keywords: Tuberculosis; disseminated intravascular coagulation; acute respiratory distress syndrome; hemophagocytosis; early treatment